Sovereign debt vulnerabilities in Asia and the Pacific - Benno Ferrarini; Suzette Dagli; Paul Mariano (Asian Development Bank (ADB), 2023)
Three major global crises since 2008 have pushed up public and external debt ratios and associated risks across much of Asia and the Pacific. This is confirmed by debt ratio projections and evidence of widening pockets of vulnerability picked up by regional heat maps in this paper. By and large, the outlook is not yet suggestive of a widespread debt crisis looming in the region, and risks continue to be highest for economies that have long been struggling with unsustainably high debt because of structural and other challenges that well precede the recent pandemic and other crises. However, even for economies with a seemingly benign outlook, it is increasingly difficult to envisage just how more widespread fiscal pressure and debt distress could be averted indefinitely. A most challenging global environment is hampering growth while raising the cost of borrowing and need for fiscal spending. The premise for restoring public finances and ensuring their sustainability after the pandemic crisis was for exactly opposite conditions to prevail.
Keywords: H63; H68; 330; sovereign debt sustainability; public debt; external debt; debt heat map